Modelling droplet heat and mass transfer in aero-engine bearing chambers - Gaviria Arcila, Dafne (2020)
Bearings are critical elements of aero-engines because they support the axial and radial loads of the turbomachinery and allow the transfer of the engine thrust forces onto the airframe. The bearings are enclosed by a chamber to avoid oil leakages to other parts of the turbine. Inside bearing chambers, we can find a mixture of air and oil, where the oil has the function of cooling and lubricating the bearing elements and the chamber walls. This oil can be found in many forms; one of them (at one extreme end of the spectrum and which we try to avoid) is droplets, which travel across the chamber and interact with the swirling air (core flow). The droplet’s interaction within the hot core flow might lead to the evaporation of the oil droplets, which is highly undesirable. The two-phase flow inside bearing chambers has been studied by two main research groups, the Gas Turbine and Transmission Research Centre (G2TRC) at the University of Nottingham and the Karlsruhe Institute of Technology (KIT) in Germany, who studied the thin film formation and droplet–film interaction (Kakimpa et al., 2014, Peduto, 2015), the flow of isothermal droplets in bearing chambers (Chen et al., 2011a, Farrall et al., 2007, Farrall et al., 2006, Peduto, 2015) and the heat transfer mechanisms between the oil droplets and the surrounding air (Adeniyi, 2015, Rosenlieb, 1978, Sun et al., 2016a, Sun et al., 2016b), with one historical paper and some recent Chinese contributions from outside these groups. However, the evaporation process and its effect on the performance of the chamber lubrication and thermal management have received little to no attention. Therefore, the investigation of the heating process of oil droplets in high-speed swirling flow has been identified here as a relevant niche for research, with questions on the thermal role of droplets in modifying chamber temperature as well as the risk presented by them as the temperature of the core keeps rising. Such a study will enable designers to better account for the need, or not, to design more carefully for droplets with a view to limiting their formation, accounting for their roles on the overall chamber temperature and/or better controlling their journey through the system. The aim of this research is hence to analyse the process of oil droplet evaporation under conditions relevant to an aero-engine bearing chamber. The ultimate goal of developing a model to accurately predict the oil–air heat and mass transfer mechanisms in the core flow region is pursued. Additionally, a better understanding of the flow inside an oil droplet and how this affects evaporation is sought. This prediction can be significant because, apparently, only a few people have studied this before (Rosenlieb, 1978). This research presents the results of a numerical study of the evaporation process of a single droplet under bearing chamber temperature and airflow conditions. The two-phase flow is simulated using the volume of fluid (VOF) method approach in the commercial ANSYS environment into which the D-square law evaporation model was implemented with a user-defined function (UDF). This model is validated using previously published results for fuel droplets in air (Daı̈f et al., 1998, Nomura et al., 1996). The validated model is then applied to the investigation of smaller droplets, which are representative of those found in bearing chambers. Different conditions are studied in a parametric study that evaluates the droplet evaporation process for a range of representative conditions. The oil evaporation rate and the evolution of the temporal reduction of the droplet’s diameter are quantified, in relation to air velocity and the droplet core’s temperature, for example. It is concluded that droplets with an initial diameter of less than 200 m (which may remain in the chamber core region for more than 0.3 s) are likely to evaporate completely; this is significant because these can be considered relatively ‘large’ droplets in the chambers we studied. Droplets with diameters smaller than 100m all evaporate very quickly. The evaporation rate is higher for droplets exposed to a higher velocity convective flow. The issue is therefore found to be very tangible. This study estimates the droplet’s heat and mass transfer and the associated phase change in a bearing chamber. The study also provides a best practice to predict the behaviour of small droplets under the effects of high-temperature and high-velocity convective airflows. This work estimated the vapour concentration needed to reach the flammability limits for droplets of PEC5 travelling in the core flow of bearing chambers. The research found that the vapour concentration in the bearing chamber is lower than the flammability range. Additionally, it provides a calculation for the amount of vapour produced by different sized droplets of oil in bearing chamber conditions, as well as the estimation of the lifetime of oil droplets in bearing chamber conditions. In this analysis, an internal convective flow was found in the heating-up and phase-change periods. The phase-change stage showed bubble formation inside the droplet with vortices associated with this effect. In some cases, the bubbles collapsed whilst releasing a portion of liquid, which sometimes caused the formation of a small secondary droplet. The radiation heat transfer was analysed from a parametric study to observe whether the radiation affects the heat and mass transfer from the environment to the droplet, which is travelling in the core flow. Radiation in the environment might have different effects on droplet evaporation. Firstly, it was noticed that the evaporation rate, at the beginning of the evaporation process, might be lower in a case that does not include radiation. Furthermore, radiation affects the heating up period and it might also affect the oil vapour distribution around the droplet’s surface at the beginning of the evaporation process as well as the droplet’s internal flow field. Moreover, we noticed that when the evaporation process is prolonged, radiation has no effect on the evaporation rate. In addition, it was observed that radiation might increase the droplet’s internal velocity. Finally, it must be highlighted that the present method was successfully validated against the correlations proposed in the literature, showing a good agreement with the theory used to formulate the correlations as mentioned above. Therefore, this confirms that the present study gives us the means to evaluate oil droplet evaporation in aero-engine bearing chambers.